Correction: Metal-free [3+3] benzannulation of 1-indanylidene-malononitrile with Morita–Baylis–Hillman carbonates: direct access to functionalized fluorene and fluorenone derivatives. Issue 94 (18th November 2020) - Xie, Ya-Sa; Huang, Run-Feng; Li, Ran; Zhang, Chuan-Bao; Fu, Ji-Ya; Zhao, Li-Li; Yuan, Jin-Fang
Abstract : Correction for 'Metal-free [3+3] benzannulation of 1-indanylidene-malononitrile with Morita–Baylis–Hillman carbonates: direct access to functionalized fluorene and fluorenone derivatives' by Ya-Sa Xie et al., Chem. Commun., 2020, 56, 1948–1951, DOI: ; 10.1039/D0CC00143K .